A miniaturized device for the measurement of sheet-metal formability using digital image correlation - Leonard, Martin Eduardo (2018)
A laboratory-scale device to obtain forming-limit diagram data was designed to utilize the Marciniak and Kuczynski (MK) sample geometry. The design uses a high-resolution photographic camera, automatic trigger, and light-emitting diode (LED) lighting to record the time history of deformation calculated with the digital-image correlation technique. Because the testing device was miniaturized, it was possible to halt the forming experiments at intermediate strains and recrystallize the MK carrier blank. This permits large formability strains to be obtained without cracks developing at the carrier blank's central hole, an advantage over full-size specimens and conventional testing rates. A number of initial experiments were performed on a zinc alloy sheet (Zn-Cu-Ti) over the entire forming-limit range (-0.5 ≤ ϵ2/ϵ1 ≤ 1), and the strain fields reduced employing the Bragard criterion to obtain limit strains. These results are compared favorably to previous data of this material obtained with a hemispherical, Nakazima, punch and a circle-grid pattern.